Photocatalyst‐Free Visible‐Light Induced Radical Difluoromethylation/Cyclization Cascade Reaction for the Synthesis of Difluoromethylated Oxindoles with Difluoromethyl Phenoxathiinium Salt - Long, Hong‐Xin; Liu, Guo‐Kai (European journal of organic chemistry, 2024)
A photocatalyst‐free photoinduced radical difluoromethylation approach for the convenient synthesis of difluoromethylated oxindoles from N‐arylacrylamides with difluoromethyl phenoxathiinium salt (PT‐CF2H+BF4−) was developed, this transformation involves radical difluoromethylation/cyclization cascade process and features photocatalyst‐free, mild reaction conditions, broad substrate scope and good functional groups tolerance. With this method, a wide variety of N‐arylacrylamides were successfully converted to desired difluoromethylated oxindoles in good to excellent yields. A photocatalyst‐free visible‐light induced radical difluoromethylation approach for the convenient synthesis of difluoromethylated oxindoles from N‐arylacrylamides with difluoromethyl phenoxathiinium salt (PT‐CF2H+BF4−) was achieved. This transformation involves radical difluoromethylation/cyclization cascade process and features mild reaction conditions, broad substrate scope and good functional groups tolerance. Using this method, a wide range of difluoromethyl‐modified oxindoles was successfully synthesized in moderate to good yields.